(untitled) (Semiárida, 2025)
The South West of Buenos Aires (SWBA) region has climatic and soil variability that differentiates it from the rest of the province of Buenos Aires. The SWBA is part of the semi-arid, arid, and sub-humid-dry region of the country and differs from the rest of the province in terms of its primary productive potential and limitations. Wheat production is the most important activity in the area. It is a winter crop deeply rooted among producers from a cultural perspective (on the supply side) and due to consumption habits (on the demand side). Depending on market prices and weather conditions, it usually yields low profitability. Drought is one of the factors that has been affecting productivity. The objective of this study is, first, to investigate producers’ perceptions regarding safflower cultivation. For this, a workshop is held, a tool framed within the Participatory Rural Diagnosis (PRD) methodology. Safflower, due to its characteristics in terms of soil requirements, growing season, among others, competes with wheat. Furthermore, it is drought-resistant and has flour and oilseed properties. According to recent agronomic studies, it can adapt very well to the agroecological conditions of the SWBA, allowing the diversification of the regional production matrix. Secondly, the aim is to explore the crop’s potential for incorporation into the oil industry. In this case, an interview is carried out with a key representative of the region.